INTERAKTIF ILMU PENGETAHUAN ALAM (IPA) PADA SDN 28/IX TANJUNG PAUH - Louis, Ahmad; Huda Aminuddin, Fattachul; Paramiza, Theza (FORTECH (Journal of Information Technology), 2023)
Learning media are tools for the teaching and learning process that can be used to stimulate thoughts, feelings, attention and abilities for learning. Natural Science (Science) lessons are a field of study that studies the universe, in learning activities teachers play a very important role in teaching. So that the teaching and learning process is not monotonous or rote, it is necessary to have multimedia-based learning media, thereby creating an interesting, interactive and fun learning process in following these subjects, especially about living things. Based on observations made by researchers at SDN 28/IX Tanjung Pauh, especially for grades one to three, the learning media used is still not appropriate, so science learning outcomes are still low and students lack interest in following lessons. Based on the research conclusions, it shows that science learning media applications can be used by teachers in multimedia-based learning facilities.